The blood-brain barrier in neuropsychiatric disorders - GREENE, CHRIS (Trinity College Dublin. School of Genetics & Microbiology. Discipline of Genetics, 2018)
Schizophrenia is a severe and disabling mental disorder that affects approximately 1% of the population. Such is the heterogeneous nature of the disease that genetic, neurobiological and environmental factors all contribute to disease progression. The vasculature of the central nervous system (CNS) forms a tight barrier that limits the movement of molecules and ions from the blood to the brain. This blood-brain barrier (BBB) is critical for proper function of the CNS as well as protecting neural tissue from damaging serum components, pathogens and anaphylatoxins. Accumulating evidence indicates that microvascular anomalies are a common pathological finding in individuals with schizophrenia however, the consequences of alterations of BBB components in schizophrenia progression and symptomatology has not been explored. Work in this thesis addresses the role of the important BBB tight junction protein, claudin-5, in the context of schizophrenia. First, it is shown that a variant in the claudin-5 gene is associated with schizophrenia in individuals with 22q11 deletion syndrome (22q11DS), a group that are haploinsufficient for claudin-5 and up to 25 times more likely to develop schizophrenia. The variant produced a dysfunctional claudin-5 protein with up to 50 % less claudin-5 protein compared to normal. Additionally, post-mortem analysis of the brains of schizophrenic patients revealed aberrant, discontinuous expression of claudin-5, especially in individuals with the claudin-5 variant compared to age-matched controls. Next, using in vitro models of the BBB it is shown that anti-psychotic medications dose-dependently increased claudin-5 expression in vitro and in vivo and enhanced barrier properties. Using preclinical mouse models, the impact of reduced claudin-5 levels in the development of psychiatric behaviours was explored. It is shown that targeted suppression of claudin-5 with an adeno-associated virus (AAV) containing a doxycycline-inducible shRNA targeting claudin-5 transcripts in the mouse brain resulted in localised BBB disruption. Down-regulation of claudin-5 induced behavioural changes with impairments in learning and memory tasks and increased depressive-like behaviours including reduced grooming time and social interaction. Furthermore, by generating a novel doxycycline-inducible claudin-5 knockdown mouse, the link between claudin-5 suppression and psychosis is further explored through a distinct behavioural phenotype that revealed impairments in learning and memory, anxiety-like behaviour, and sensorimotor gating. Additionally, these animals developed seizures and had a more pronounced loss of BBB integrity with macromolecule leakage and astrogliosis. Finally, the mice died after 3-4 weeks of constant claudin-5 suppression, reinforcing the crucial role of claudin-5 in normal neurological function. Lastly, it is known that over one third of the genome displays a circadian rhythm. Circadian rhythms control diverse biological functions including the sleep-wake cycle and are frequently disrupted in psychiatric disorders. The concluding section of this thesis shows that the BBB is regulated by circadian rhythms with claudin-5 expression being activated by the clock transcription factor BMAL-1 that produces temporal changes in BBB permeability. Together, this data suggests that BBB disruption may be a modifying factor in the development of schizophrenia and that drugs directly targeting the BBB may offer new therapeutic opportunities for treating this disorder.
APPROVED
Keywords: Blood-brain barrier; Tight junction; Schizophrenia